2017
DOI: 10.1021/acs.jpca.6b12608
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Morphology of Frozen Mixed Nitrate–Salt Solutions

Abstract: Surface chemistry on ice can play an important role in atmospheric composition, but uncertainties in the chemical partitioning within ice samples has hindered the development of accurate models of these systems. Using Raman microscopy, we examine the nitrate distribution in ice and liquid samples containing environmentally relevant concentrations of sodium chloride, sodium bromide, and sea salt analogue Instant Ocean. Nitrate is enhanced at the surface compared to in the bulk in all frozen samples but to diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 22 publications
0
21
1
Order By: Relevance
“…Nitrate is a product of N 2 O 5 hydrolysis that suppresses the N 2 O 5 uptake onto particles, , while chloride is required for ClNO 2 production . Chloride and nitrate are expected to be enriched within brine pockets on the snow grain surface. , Model simulations by Wang et al for Ann Arbor, MI, also suggested that the snowpack ClNO 2 flux is dependent on the temperature due to changes in the snow surface brine fraction, with more ClNO 2 lost to hydrolysis at higher temperatures, leading to a more negative (downward) flux. Although the experimental ClNO 2 fluxes in this study showed no correlation with the air temperature, transformations in the snowpack morphology, caused by melting and/or re-freezing, likely impacted ClNO 2 production as this decreases the available surface area for multi-phase reactions. , This motivated snow chamber experiments in which snow samples of differing physical and chemical properties were exposed to N 2 O 5 , and resulting ClNO 2 was monitored (Section ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nitrate is a product of N 2 O 5 hydrolysis that suppresses the N 2 O 5 uptake onto particles, , while chloride is required for ClNO 2 production . Chloride and nitrate are expected to be enriched within brine pockets on the snow grain surface. , Model simulations by Wang et al for Ann Arbor, MI, also suggested that the snowpack ClNO 2 flux is dependent on the temperature due to changes in the snow surface brine fraction, with more ClNO 2 lost to hydrolysis at higher temperatures, leading to a more negative (downward) flux. Although the experimental ClNO 2 fluxes in this study showed no correlation with the air temperature, transformations in the snowpack morphology, caused by melting and/or re-freezing, likely impacted ClNO 2 production as this decreases the available surface area for multi-phase reactions. , This motivated snow chamber experiments in which snow samples of differing physical and chemical properties were exposed to N 2 O 5 , and resulting ClNO 2 was monitored (Section ).…”
Section: Resultsmentioning
confidence: 99%
“…For the snow samples tested here, the bulk snowmelt [Cl – ] was likely not limiting, within the time period of exposure, because ClNO 2 production was not sensitive to this variable. In addition, no correlation was observed with bulk snowmelt [NO 3 – ] (Table S3), which can suppress the N 2 O 5 uptake , and is likely enriched in brine pockets at the saline ice surface. , The snow chloride concentration, however, defines the calculated snow grain brine volume fraction, thereby indirectly affecting the predicted ClNO 2 yield. Following the methodology presented by Wang et al, we calculate the predicted ClNO 2 yields to range from 0.1 to 0.5 for the February 17 snow samples and from 0.3 to 0.5 for the February 18 snow samples, excluding the Field + Salt sample, for which the high [Cl – ] result in calculations of 100% brine (complete snowmelt) due to freezing point depression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, monolayers of organic species can greatly increase the surface activity of other organic molecules. 29−31 Microscopic studies of frozen samples show that bromide enhances nitrate concentrations at ice surfaces compared to in bulk ice, 16 and that organic dyes are distributed differently in ice samples containing millimolar concentrations of salts compared to in deionized (DI) water. 27 In this work, we investigate the distributions of liquid water and solutes in laboratory-prepared proxies for sea ice containing various amounts of OM.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Cotter et al (2003) proposed a possible mechanism of snow nitrate (NO3 − ) photolysis to produce NO/NO2, and this mechanism has been confirmed by laboratory research (Boxe et al, 2003;Jacobi and Hilker, 2007) and many field observations (Jones et al, 2000;Dibb et al, 2002). More complicated and further improved mechanism can be found in the following researches (Wren et al, 2011;Domine et al, 2013;Morenz and Donaldson, 2017) and review paper by Bartels-Rausch et al (2014).…”
mentioning
confidence: 79%